Menggali kekuatan karakter: conscientiousness berperan pada orientasi masa depan dan keputusan karir siswa SMK - Iswinarti; Siti Suminarti Fasikhah; Nurhuda Alfina Layalin (Universitas Muhammadiyah Malang, 2023)
Career choices is a central role in an individual’s life, especially for vocational school students. For this reason,understanding the elements that influence career decisions becomes essential to ensure that individuals can formulateaccurate and aligned choices with their long-term aspirations. Future orientation is among the factors impacting careerchoices. Students who possess a strong sense of future orientation enhance their capacity to make informed careerdecisions. Conscientiousness is thought to have an important role in increasing the influence of future orientation on thecareer decisions of female vocational high school students. The purpose of this study was to determine the moderatingeffect of Conscientiousness on the effect of future orientation on career decisions. The research subjects were 194students who were in class XII at SMK in Ponorogo. Data were collected using the Career Decision Scale, FutureOrientation Scale, and the Big-five personality scale NEO-PI-R. The Moderate Regression Analysis (MRA) method wasemployed for data analysis. The findings of the research indicate that Conscientiousness has the capability to amplifythe influence of future orientation on the career choices made by vocational school students in Ponorogo.